THE DIDACTIC DESIGN OF NATURAL SCIENCES LEARNING ABOUT WATER CYCLES IN 5TH GRADE ELEMENTARY SCHOOL - Arumsari, Kanti (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
This research is motivated by the findings of learning barriers experienced by students in Classes V and VI of elementary school from the results of a preliminary study. Students do not yet understand the concept of the occurrence of water cycle so students find it difficult to work on identifying learning obstacles in the water cycle topic. This obstacle is caused by learning that does not pay attention to the nature of natural science learning and meaningful learning for students. Students are not actively involved in finding a concept but instead only receive information. Therefore, students' understanding of the water cycle topic is not built because the learning process is meaningless. This research aims to design a didactic design consisting of a lesson design which pays attention to the science process skills, the nature of natural science learning and meaningful learning. This didactic design has been validated by experts to get a better didactic design. The research method used is qualitative research methods while the data collection techniques used are observation, interviews, and documentation. This research produced three lesson designs from the results of the learning obstacle research analysis, namely: lesson design 1 understanding the role of water for living creatures, lesson design 2 introducing water elements and processes, and lesson design 3 understanding caring attitudes towards water conservation